Oz the great and powerful: The Junior Novel - Rudnick, Elizabeth; Kapner, Mitchell; Lindsay-Abaire, David; Baum, L. Frank (Lyman Frank), 1856-1919. (New York : Disney Press, 2013)
Oscar Diggs finds himself in the land of Oz where the inhabitants think he is a powerful wizard until three witches begin to question his abilities.
Keywords: Wizards -- Juvenile fiction; Oz (Imaginary place) -- Juvenile fiction; Film novelizations; Fantasy fiction